On-Farm Study on Intercropping of Hybrid Maize with Different Short Duration Vegetables in the Charland of Tangail (Bangladesh Agronomy Journal, 2016)
An experiment was conducted in charland at the Multi Location Testing (MLT) site Bhuapur, Tangail during 2012-13 and 2013-14 under AEZ-8 to find out the suitable intercropping system of hybrid maize with different short duration vegetables with economic return. The experiment was laid out in RCB design with six dispersed (six farmers field) replications. The hybrid maize (ver. BARI Hybrid maize-7), potato (Diamant), spinach (local), red amaranth (BARI Lalsak-1), Radish (BARI Mula-1) were used as the planting materials. Five treatment combinations viz. T1= Sole Maize, T2= 100% Maize (maize paired row) + Potato (var. Diamant), T3= 100% Maize (maize paired row) + Spinach (var. local), T4= 100% Maize (maize paired row) + Red amaranth (var. BARI Lalshak-1) and T5= 100% Maize (Maize paired row) + Radish (var. BARI Mula-1) were studied. Maize grain yield in intercropped combination varied from 5.59-7.62 t ha-1. But the highest grain yield (8.17 t ha-1) was obtained from sole maize. Maize equivalent yields in the intercrops situation ranged from 11.39-19.68 t ha-1 where highest maize equivalent yield 19.68 t ha-1 was recorded from the treatment T3 (100 % maize + spinach). The same combinations also gave highest gross return (Tk. 373930 ha-1) and gross margin (Tk. 258585 ha-1) as well as benefit cost ratio (3.24). Though highest grain yield was recorded from sole maize but equivalent yield and economic return was much lower than the treatment T3.Bangladesh Agron. J. 2015, 18(2): 65-69